2003
DOI: 10.1002/mc.10154
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of prostate‐specific antigen (PSA) in prostate cancer cells expressing mutant p53 is associated with tumor metastasis

Abstract: The underlying basis for rising levels of prostate-specific antigen (PSA) in prostate cancer is not fully understood, but attention has turned to the possibility that loss of normal p53 function might be directly involved. We have investigated the relationship between p53 function and PSA expression using in vitro and in vivo approaches. Three prostate cancer-derived p53 mutants (F134L, M237L, R273H) were introduced into LNCaP prostate cancer cells and stable transfectants established. Expression of mutant p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Since orthotopic tumor growth was accompanied by increased vascularisation and vascular leakage [20] ( Fig. 2) this could be another factor advancing metastatic burden [43,46]. Functional changes due to expression of cell adhesion molecules (CAM) can also modify cellular behaviour.…”
Section: Discussionmentioning
confidence: 98%
“…Since orthotopic tumor growth was accompanied by increased vascularisation and vascular leakage [20] ( Fig. 2) this could be another factor advancing metastatic burden [43,46]. Functional changes due to expression of cell adhesion molecules (CAM) can also modify cellular behaviour.…”
Section: Discussionmentioning
confidence: 98%
“…However, the emerging evidence demonstrates that p53 also plays a crucial role in regulating key stages of the metastatic progression (4,6). In PCa, although some studies have showed that mutant p53 gain of function promoted cancer development and metastasis (5,(35)(36)(37)(38), there are hardly any studies on the role of WT-p53 in PCa metastasis.We found that WT-p53 repressed invasion and migration, and suppressed EMT, which is a key step of the progression of tumor cell metastasis, and cancer stem cells properties in PC-3 cells, which might be the critical drivers of tumor progression and metastasis (16,17). Zhou et al (39,40) have found that the combined deficiency for p53 and Rb in prostate epithelium results in invasive and highly metastatic prostate carcinogenesis, and preferential malignant transformation of prostate stem cell compartment by combined deficiency by p53 and Rb indicates a critical role of these genes in the regulation of prostate stem cells during ontogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…5A) was due to the recovery of p53 (see Fig. 4A), HeLa and Caski cells were transiently transfected with a dominant negative p53 mutant (20). Expression of the dominant negative p53 effectively inhibited the ability of the calpain inhibitor to reduce viability of HeLa and Caski cells (Fig.…”
Section: A Calpain Inhibitor Restored Rb Protein Levels Repressed E6mentioning
confidence: 92%
“…Plasmids encoding Rb K810A and Rb were generated from pCDNA3.1 Rb by site-directed mutagenesis (14). Dominant negative p53 (pRc/CMV-R273H) has been described previously (20). Vector controls used pcDNA3.1 (Invitrogen).…”
mentioning
confidence: 99%